Transformation of an archival recording of a neoclassical ballet Hamlet into a new artistic dance video Hamlet Revisited - Sečak, Svebor (Monitor ISH, 2021)
This text is a distillation of the author’s exegesis that is an integral part of the PhD in Creative Practice project and is complementary to the dance video titled Hamlet Revisited. It shows the transformation of a video recording of the author’s own choreography of the ballet Hamlet into a contemporary post-postmodern dance video DVD Hamlet Revisited, answering the following research question: How to transform an archival recording of a neoclassical ballet performance into a new artistic dance video by implementing postmodern philosophical concepts? The goal of the project is to elucidate the transformation of Hamlet to Hamlet Revisited, from a neoclassical choreographic approach to the recent postmodern approach that traverses into a transmodern dance video of an eclectic blend of styles and techniques in accordance with the paradigm of digimodernism.
Keywords: Balet; Hamlet (balet); video produkcija; Video umetnost; vizualna umetnost